GERAKAN MAHASISWA DALAM KEMELUT POLITIK DI MYANMAR: PERGULATAN MEWUJUDKAN KEBEBASAN - Mohammad Maiwan (Jurnal Ilmiah Mimbar Demokrasi, 2014)
The dynamic of the student movement in Myanmar influenced by social and political factors. The emergence of their movement as a direct response of the condition of the nation. In the past involvement of student leaders in various organizations provide an important contribution to the emergence of anti-colonial movement, which culminated in independence in 1948. After independence student movement emerged as a moral force in correct of government policies. From the reign U Nu liberal democracy in 1948-1958, 1960-1962, and then under the military regime in 1958-1960 and 1962-2011, until under quasi-military rule today. The existence of differences between student and regime causes their had clashed and suppressed in 1958, 1962, 1974, 1975, 1988. At a certain stage, their movement give a pressure on the regime